Prevalencia de control insuficiente de factores de riesgo en prevención primaria de patología coronaria - Ugalde C., Diego; Urquieta E., Javiera (Revista Hospital Clínico Universidad de Chile, 2009)
Background: Coronary artery disease is an important cause of mortality and morbidity in Chile, there are known risk factors for its beginning and progress, controling them could improve prognosis. There is insufficient information on risk factor control in primary prevention, and a descriptive study was designed. Objectives: Describe the extent of use of primary prevention measures on risk factors of coronary artery disease on Chilean patients hospitalized at the Clinical Hospital of the University of Chile on prior outpatient period. Patients and methods: A survey was applied to 63 patients on their hospitalizations rooms. Blood pressure and Low Density Lipoprotein data were obtained from their charts. A database was created and risk factors were analyzed independently. Results: 100% of uncontrolled hypertensive patients were undertreated. 31.25% smokers had not received advise on cessation. 48% of overweight and 37.5% of obese patients were under no management. 34% of sedentary patients reported no advise on physical exercise from their regular physicians. Conclusions: The current study reveals several risk factors being undertreated, however it presents important limitations, studies with more patients may be required to confirm these findings. Physicians should be aware of undertreatment.